Progressive Education in Indonesia: Insight from Soedjatmoko Thought - Hendri Hermawan Adinugraha (Tarbawy : Jurnal Pendidikan Islam, 2020)
Education is the investment of long-term to prepare human resources quality to face the challenges of the future. As explained by Soedjatmoko what kind of traits and abilities Indonesian human beings should have in the future. Of course, because some of the necessary features and abilities are obvious. First, we must be well informed. Second, the ability to be creative about new challenges, along with an ability to anticipate developments and innovate. Third, Indonesians must have self-esteem and self-belief, based on strong faith. Looking at the explanation, it seems clear that the purpose of actual education is a high sense of appreciation for the reality of humanity. Humanitarianism according to Soedjatmoko is a continuation of humanism and has a basic orientation towards human freedom and welfare. Soedjatmoko has considerable attention to the Indonesian people who from the beginning until now are in the process of educational development. To realize his thoughts, Soedjatmoko emphasized ethical principles; liberation, responsibility, consensus, empathy and tolerance, nonviolence, modernization, and religion. Soedjatmoko’s concerns and ideas are inspiring, not just for those who have interacted with him. That Soedjatmoko’s ideas and analysis as a whole his work is focused on the human aspect as the heart of civilization.